Health and environmental impact assessment of landfill mining activities - Zari, Mohammed (2024)
The adoption of landfill mining (LFM) has the potential to reduce the negative environmental effects of landfills while also recovering critical and secondary raw materials, energy, and land space by a series of on-site mechanical operations. However, there is a fundamental lack of understanding of how these activities could impact the environment and human health during LFM mining operations through atmospheric transport of contaminants. Therefore, this research aims to bridge this gap and optimize the benefits of LFM activities by shedding light on the potential health and environmental impacts associated with these practices.